Endoscopic lumbar discectomy and minimally invasive lumbar interbody fusion: a contrastive review - Chao Yuan; Jian Wang; Yue Zhou; Yong Pan (Videosurgery and Other Miniinvasive Techniques)
Both percutaneous endoscopic lumbar discectomy (PELD) and minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) have been demonstrated as two common and effective choices for lumbar disc herniation (LDH) minimally invasive surgery. In order to get a better understanding of these two procedures, we made this contrastive review. By looking up recent literature and combining it with our clinical practice, the indications/contraindications, advantages/disadvantages as well as complications/recurrences of PELD and MIS-TLIF were summarized in this review. It was concluded that PELD and MIS-TLIF are safe and effective minimally invasive operative techniques for symptomatic LDH treatment. A better understanding of these two procedures will help to improve clinical outcomes by selecting proper indications, and also benefit the further development of minimally invasive spine surgery.